The Current State, Threats, and Challenges of Using Generative Artificial Intelligence to Support Student Learning in Higher Education institutions - Bruyaka, Alina; Kovalenko, Valentyna; Marienko, Maiia; Semerikov, Serhiy; Shyshkina, Mariya (Educological discourse, 2025)
The article aims to analyze the current state, threats, and challenges of using generative artificial intelligence (GAI) to support the educational activities of students in higher education institutions. The study relevance is due to the rapid development of GAI technologies and their penetration into the academic environment, which requires a deep understanding of their potential and associated risks. The study used theoretical methods, including a systematic analysis of scientific sources, synthesis, and generalization of existing experience. This allowed authors to identify key trends in implementing GAI in the educational process. The authors identify three primary, interrelated areas of development: the formation of digital and AI literacy among students, the development of innovative models of individualization of learning, and the implementation of ethical and policy-regulatory frameworks. The main threats and challenges were identified based on the analysis of pedagogical experience gained during the organization and conduct of international conferences, webinars, seminars, and practical classes from 2023 to 2025. Among them, risks to academic integrity were identified, such as plagiarism and uncontrolled use of AI, as well as methodological gaps in teaching that require developing new approaches. The study results show that AI has significant potential for personalizing learning trajectories, automating assessment, and providing adaptive content. Still, its practical implementation is possible only if the appropriate competencies are formed in teachers and students, and explicit ethical norms are created. The authors note that further research should focus on developing practical methods for using AI to develop critical thinking and creativity, as well as studying its impact on motivation and knowledge assessment. This will allow the practitioners to maximize the benefits of new technologies and minimize their negative consequences. The conclusions emphasize that the successful integration of AI requires a comprehensive approach that includes changes in both the technological and educational-methodological planes.